Analysis of the model application of mechanical equipment for hydrothermal treatment - P. Junga; T. Vítěz; P. Mach; P. Trávníček (Research in Agricultural Engineering, 2013)
Two model applications of mechanical equipment for hydrothermal treatment were analysed. Alternative 1 consisted of a treatment output of 2,000 Mg of processed material, the annual compost production of 1,000 Mg, total capital expenditure of 15,838,000 CZK, unit capital expenditure of 7,919 CZK per 1 Mg of processed material and annual operating expenses of 1,300,000 CZK. The net present value (NPV) is 1,482,800 CZK, the internal rate or return (IRR) totals 7.6% and the discounted payback time (Tsd) is 16.9 years. Alternative 2 employing the mechanical equipment proved a potential increase in the treatment output to 2,600 Mg, and an increase in the compost production to 1,300 Mg thanks to the shortened intensification of composting. At the same time, the total capital expenditure rose to 18,997,000 CZK, the operating expenses rose to 2,080,000 CZK. The unit capital expenditure of alternative 2 amounts to 7,306 CZK per 1 Mg of the treatment output. The NPV totals 6,984,200 CZK, IRR is at 10.7% and Tsd totals 11.8 years.